Massekke Tradition: Syncretism of Local Culture and Islamic Sharia in the Fishermen’s Community at the Spermonde Archipelago, South Sulawesi - Zainuddin; Salle; Hasbuddin Khalid (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
Zakah is an obligation for Muslims which is strictly regulated in Islamic law, but in Muslim communities in Indonesia, its implementation cannot be separated from local traditions. This research discusses the Massekke tradition in implementing Zakah and cultural syncretism in the Massekke tradition in fisherman communities in the Spermonde Islands, South Sulawesi. This socio-juridical research uses a qualitative approach. The analysis technique uses interactive models. The results show that the fisherman's community in the Spermonde Islands recognizes two types of Zakah, namely sekke fittara (Zakah al-fitr) and sekke warang parang (Zakah on the property). Zakah payments are made in the middle of the month of Ramadan until the end of the month of Ramadan in the form of rice or money accompanied by pelleng (candlenut) and candles as a symbol which means that the Zakah payer has a clear heart when paying Zakah, which begins with mappacci as a form of purification of property, body and soul. Mustahik ( recipient of Zakah) among fisherman